Clinicopathological relationship between PM2.5 exposure and acute exacerbations of chronic obstructive pulmonary disease - Anfeng Cui; Yingying Shao; Yang Wang; Haodong Wang; Jiayi Song; Caiji Liu; Ningning Shen; Zhiqing Yang; Wangliang Zhang; Tiane Luo; Chen Wang (Ecotoxicology and Environmental Safety)
Objective: This study investigates the association between fine particulate matter (PM2.5) exposure and acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Methods: A retrospective analysis was conducted on 1284 AECOPD hospitalizations at Shanxi Medical University's Second Hospital from 2018 to 2022. This data was paired with Shanxi's average monthly PM2.5 data from the Tracking Air Pollution in China (TAP) dataset. Correlations between PM2.5 levels and AECOPD clinicopathological features were assessed using ANOVA and Spearman’s correlation. Results: Higher PM2.5 concentrations were observed during February-April and November-January, correlating with increased AECOPD admissions (r = 0.754), outpatient visits (r = 0.799), emergency visits (r = 0.447), and ICU transfers (r = 0.860). Among the patients, 76.5 % were smokers and 68.4 % were over 60 years old. Inflammatory markers (leukocyte and neutrophil counts, eosinophil percentages, C-reactive protein), D-dimer levels, PaCO2, and pulmonary fibrosis indicators showed positive correlations with PM2.5 levels, whereas Pulmonary Function measures (FEV1/ FVC, FEV1 %) and PaO2 showed inverse correlations. Conclusion: Elevated PM2.5 exposure significantly increases the risk of AECOPD, linked to heightened inflammation, pulmonary fibrosis, and diminished pulmonary function, and the majority of these patients are over 60 years old or are smokers. This study provides valuable theoretical and practical insights for the proactive prevention and management of AECOPD in clinical settings.